Preparation and Characterization of Cellulose Nanofibril Films from Wood Fibre and Their Thermoplastic Polycarbonate Composites - S. Panthapulakkal; M. Sain (International Journal of Polymer Science)
The aim of this study was to develop cellulose-nanofibril-film-reinforced polycarbonate composites by compression molding. Nano fibres were prepared from wood pulp fibres by mechanical defibrillation, and diameter distribution of the fibres produced was in the range of 1–100 nm. Nanofibre films were prepared from the nanofibre suspensions and were characterized in terms of strength properties, crystallinity, and thermal properties. Strength and modulus of the nano fibre films prepared were 240 MPa and 11 GPa, respectively. Thermal properties of the sheets demonstrated the suitability of processing fibre sheets at high temperature. Tensile properties of the films subjected to composite-processing conditions demonstrated the thermal stability of the fibre films during the compression molding process. Nanocomposites of different fibre loads were prepared by press-molding nano fibre sheets with different thickness in between polycarbonate sheet at 205°C under pressure. The tensile modulus and strength of the polycarbonate increased with the incorporation of the fibres. The strength of the thermoplastic increased 24% with 10% of the fibres and is increased up to 30% with 18% of the fibres. Tensile modulus of the polycarbonate demonstrated significant enhancement (about 100%).